An econometric analysis of the impact of macro-prudential instruments on the Nigerian economy - Central Bank of Nigeria, Research Department (Abuja, Nigeria Central Bank of Nigeria, 2016)
This study is focused on identifying the channels of macro-prudential shocks to the domestic economy; determining the size of the impact through the determination of short-and-long-run multipliers among others.
Includes bibliographical references.
oif 22/05/17
Ref.
Keywords: Macroeconomics - Econometric model; Econometrics; Economic policy; Nigeria